Study of the floating joint effectiveness in improving the press machine mechanism : an automotive industry case study - Mohd Hafiz Ruhani (2018)
Automotive is an industry that worth over 250 billions US dollars worldwide a year, with production trending towards efficiency and sustainability. Floating joint which having moderate radial play and capable of shaft centering has been selected for this study since these function of mechanisms will lead to decrease the reject number in production and it has been proved in other production line. Besides that, the effectiveness of floating joint has been proved using Cmk data comparison that shows significantly different with Cmk data of C-type joint. This activity will focus on three problems statement which are high reject number in production due to mounting bush height out of specification, measurement error due to jammed of sliding bush and error on gauge repeatability and reproducibility result due to appraiser in efficiency. Focus point for this activity by explore the cause of high reject number of mounting bush with investigate the effect of replacing C-type joint with floating joint to reduce the mounting bush height error must be the prioritized. Data before the implementation is required for effectiveness confirmation. Right understanding for selected mechanism on advantages and disadvantages is required. Result of Cmk for the changes mechanism must not be less than Cmk control value which is 1.67 to show the effectiveness of the changes.